2019
DOI: 10.1111/1556-4029.14100
|View full text |Cite
|
Sign up to set email alerts
|

Finding of Hyperostosis Frontalis Interna During the Autopsy Procedure: Forensic Issues

Abstract: Hyperostosis frontalis interna is a common phenomenon, which may have been overrated in its significance in the past, and may, currently be underrated in its significance. We present three cases of hyperostosis frontalis interna found during medicolegal autopsies and discuss their forensic considerations. The patients were all middle‐aged women with metabolic and endocrine manifestations and psychiatric ailments; thickening of the inner table of the frontal bone of the skull was found during each autopsy. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…It has been observed that before the nineteenth and twentieth centuries, there was less prevalence of HFI which contributed to less life span during that time. Thus, human longevity in recent eras, the microevolution of human endocrine regulation by sex steroids, and lifestyle changes like obesity, Type 2 Diabetes Mellitus have also contributed to the increased prevalence of HFI [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that before the nineteenth and twentieth centuries, there was less prevalence of HFI which contributed to less life span during that time. Thus, human longevity in recent eras, the microevolution of human endocrine regulation by sex steroids, and lifestyle changes like obesity, Type 2 Diabetes Mellitus have also contributed to the increased prevalence of HFI [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Hiperostozis frontalis internanın ayırıcı tanıları arasında fokal kitleler, subdural ve dural kalsifikasyon gibi patolojiler yer almaktadır. 6 Olgumuzda kronik subdural hematom kalsifikasyonu ile karışmıştır. Bu durum, olgumuzla benzer şekilde en çok menopoz sonrası kadınlarda görülür.…”
Section: Discussionunclassified
“…The condition now known as HFI was first described by Morgagni based on his autopsy of an elderly woman showing obesity and hirsutism (Morgagni, 1719). While the changes to the internal table of the frontal bone are diagnostic of HFI, more than 300 years after its initial description, the exact etiology of the condition is still unresolved (Bascou et al, 2019; Raikos et al, 2011). Several endocrine, metabolic, and neuropsychiatric signs and symptoms are reported to frequently accompany HFI.…”
Section: Introductionmentioning
confidence: 99%